Markers of low-iron status are associated with female athlete triad risk factors - Finn, E. F.; Tenforde, A. S.; Fredericson, M.; Golden, N. H.; Carson, T. L.; Karvonen-Gutierrez, C. A.; Carlson, J. L. (Medicine & Science in Sports & Exercise, 2021)
Purpose: The Female Athlete Triad (Triad) is common in female athletes. The Triad is caused by low-energy availability (EA), which is often difficult to measure and has been postulated to be associated with low-iron status. Here, we explore whether markers of low-iron status may be associated with indicators of low EA including Triad risk factors. Methods: A total of 239 female National Collegiate Athletic Association Division I athletes completed preparticipation examinations that included Triad risk factors, medication/supplement use, diagnosis of anemia, and elected to complete dual-energy x-ray absorptiometry scan to measure bone mineral density. The association of markers of low iron (defined as self-report of iron supplementation and/or history of anemia) with each component of the Triad risk assessment score was assessed by stratifying low-iron status across different levels of Triad risk category. Differences across iron status groups were assessed using Fisher exact testing. Results: Every component of the Triad risk assessment score excluding delayed menarche was associated with low-iron status. The proportion of women who reported low iron was 11.5% in the low-risk EA group compared with 50% in the moderate-risk and 66.7% in the high-risk EA groups (P = 0.02); respectively. These numbers were 11.6%, 25.0%, and 66.7% (P = 0.02) for body mass index; 9.7%, 16.7%, and 25.0% (P < 0.05) for oligomenorrhea; 10.3%, 45.5%, and 50.0% (P < 0.01) for bone mineral density; and 10.4%, 20.8%, and 30.8% (P = 0.03) for history of stress reaction or fracture. Lean/endurance athletes were more likely to have low-iron status than other athletes (15.5% vs 3.4%, P = 0.02). Conclusions: Markers for low-iron status were associated with Triad risk factors. Our study suggests that female athletes with a history of anemia or iron supplementation may require further screening for low EA.